2017
DOI: 10.1590/s1678-9946201759030
|View full text |Cite
|
Sign up to set email alerts
|

Immune development in HIV-exposed uninfected children born to HIV-infected women

Abstract: Immunological and clinical findings suggestive of some immune dysfunction have been reported among HIV-exposed uninfected (HEU) children and adolescents. Whether these defects are persistent or transitory is still unknown. HEU pediatric population at birth, 12 months, 6-12 years were evaluated in comparison to healthy age-matched HIV-unexposed controls. Plasma levels of LPS, sCD14, cytokines, lymphocyte immunophenotyping and T-cell receptor excision circles (TREC) were assessed. HEU and controls had similar LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
1
20
2
Order By: Relevance
“…Recently, a study in Brazil compared plasma cytokine profiles and immunological cell subsets in HIV exposed and non HIV exposed children from birth to 6–12 years of age. At birth, no differences in cytokine levels, B cells, or MBC subsets (including atypical MBC) were found between the groups (90). Finally, pregnant women in Papua New Guinea with high malaria exposure also had elevated frequencies of atypical MBC, but cord blood MBC subset distribution was not examined (91).…”
Section: Discussionmentioning
confidence: 92%
“…Recently, a study in Brazil compared plasma cytokine profiles and immunological cell subsets in HIV exposed and non HIV exposed children from birth to 6–12 years of age. At birth, no differences in cytokine levels, B cells, or MBC subsets (including atypical MBC) were found between the groups (90). Finally, pregnant women in Papua New Guinea with high malaria exposure also had elevated frequencies of atypical MBC, but cord blood MBC subset distribution was not examined (91).…”
Section: Discussionmentioning
confidence: 92%
“…A previous study with HEU children from Brazil also revealed similar levels of microbial translocation and inflammation markers in plasma of HEU and unexposed children. 44 In HIV-infected individuals, alterations in gut microbiota are generally linked to increased microbial translocation. 18 Although we show that HEU children present differences in gut microbiota composition, there were no signs of microbial translocation, indicating that the microbiota alterations observed in HEU children are not directly linked to microbial translocation.…”
Section: Discussionmentioning
confidence: 99%
“…The HIV-1-infected women selected for this sub-study were representative of the original HIV cohort as young, moderately immunosuppressed, without a medical history of HIV-related illnesses. Specifically, the median age at enrolment was 25 years (interquartile range (IQR), [23][24][25][26][27][28]. The women had a median CD4+ T cell count of 403 cells/ml (IQR, 313-523) and CD4:CD8 ratio of 0.44 (IQR, 0.29-0.73).…”
Section: Cohort Descriptionmentioning
confidence: 99%
“…The HIV uninfected motherinfant cohort was enrolled from a similar community. The median age at enrolment was 25 years (IQR, [23][24][25][26][27][28][29]. Infants born to HIV infected and HIV uninfected groups of women were of similar birth-weight: 3.3 kg (IQR, 3.0-3.6) vs 3.1 kg (IQR 2.9-3.5), respectively.…”
Section: Cohort Descriptionmentioning
confidence: 99%
See 1 more Smart Citation